266 Performance assessment of French guidelines for the management of STEMI patients out of cardiac critical care unit on clinical practices: insights from the e-MUST registry. (23rd September 2015) - Bataille, Sophie; Tresca, Jean-Pierre; Mouranche, Xavier; Mapouata, Mireille; Greffet, Agnès; Letarnec, Yves; Capitani, Georges-Antoine; Templier, François; Lapandry, Claude; Auger, Arnold; Dupas, François; Dubourdieu, Stéphane; et al.
Abstract : Objective: In 2006 evidence based guidelines for STEMI reperfusion strategies out of cardiac critical care unit were published in France. The objective of this program is to assess the performance of these guidelines to improve reperfusion strategies for STEMI within 2 h from onset of symptoms, thrombolysis versus primary PCI, using the e-MUST registry data in the greater Paris area. Methods: The e-MUST registry is a regional prospective prehospital database supported by the hospital governmental agency (ARHIF). It began tracking practice patterns for STEMI prehospital reperfusion strategies in 2000 in the greater Paris area. All STEMI with clinical and ECG features suggestive of less than 24 h duration, managed by prehospital medical team, are collected. The evidence based guidelines for STEMI patients managed out of cardiac critical care unit, including prehospital setting, were established in 2006 to stratify reperfusion strategies according to the presumed delay to cath lab. If the presumed door to cathlab delay is over 45 min and onset of symptom delay less than 12 h thrombolysis is recommended before transferring to a PCI capability hospital. Reperfusion strategies for STEMI within 2 h of onset of symptoms, either thrombolysis or primary PCI were compared in the registry through the years 2002, before guidelines, 2006, and 2008, after guidelines publication. Two groups of patients were studied according to the elected reperfusion strategy, Two subgroups of patients elected for primary PCI were distinguished according to the 45 min door to cathlab delay cut off. The onset of symptom to treatment mean delays, either lytic infusion or balloon inflation, were documented for each group and subgroup of patients. Résults: Greater Paris area 2002 2006 2008 p STEMI<24 h 1806 1618 1689 STEMI<2 h 1029 (57%) 1015 (63%) 1042 (62%) =0.002 STEMI<2 h reperfusion decision 940 (91%) 959 (94%) 989 (95%) =0.01 1/Thrombolysis 373 (44%) 318 (36%) 196 (21%) <0.001 Pain (onset of symptoms) to thrombolysis mean delay (min) 85 80 80 =0.018 2/PCI with less than 45 min door to cathlab delay 114 (12%) 173 (19%) 243 (26%) <0.001 Pain (onset of symptom) to balloon mean delay (min) 135 128 131 =0.54 3/PCI with over 45 min door to cathlab delay 358 (42%) 403 (45%) 481 (53%) <0.001 Pain (onset of symptom) to balloon mean delay (min) 160 161 160 =0.410 Discussion: The ratio of patients managed within 2 h of onset of symptoms has increased from 57% in 2002 to 62% in 2008. The rate of prehospital reperfusion decision has also increased from 91% in 2002 to 95% in 2008. Mean delays from onset of symptom to treatment were not significantly different from 2002 through 2008, either for thrombolysis, or for the primary PCI elected strategy within or over the 45 min door to cathlab delay cut off. Prehospital thrombolytic therapy was significantly less frequently elected, from 44% in 2002 to 21% in 2008. The ratio of primary PCI with over 45 min door to cathlab delay has significantly increased from 42% in 2002 to 53% in 2008. Conclusion: The e-MUST registry helps to assess the performance of guidelines on clinical practices and prehospital management of STEMI within 2 h of onset of symptoms. This improvement study highlights an everyday earlier management of STEMI patients and a very high rate of prehospital reperfusion decision. These are the main benefits of the registry program. Nevertheless most of physicians underestimate the door to cathlab delay. The registry should initiate a brain storming on delays and elected strategies to optimise the ratio of reperfusion within the guidelines recommended delays especially for STEMI patients fitting with the golden hour delay. Objectif(s), contexte: L'objectif de ce programme est de mesurer en Ile-de-France, par le registre e-MUST, l'évolution des stratégies de reperfusion coronaire (thrombolyse pré-hospitalière versus angioplastie primaire) des syndrome coronaires aigus ST+<2h, pris en charge en pré-hospitalier, en fonction des délais d'angioplastie primaire, dans le cadre des recommandations de la conférence de consensus sur la prise en charge de l' infarctus du myocarde aigu en dehors des services de cardiologie, diffusée en 2006. Programme: Le registre e-MUST est un registre de pratiques prospectif, développé par l'Agence régionale de l'hospitalisation en Ile-de-France depuis 2000. Il recense tous les SCA ST+<24h pris en charge en pré-hospitalier par les SAMU/SMUR de la région. La conférence de consensus sur la prise en charge des IDM aigus en dehors des services de cardiologie a été publiée en 2006. Les recommandations portent sur la stratégie de désobstruction coronaire en fonction du délai estimé d'arrivée en salle de cathétérisme cardiaque pour réaliser une angioplastie primaire. Si l'estimation du délai porte-porte cardio est supérieure à 45 min et que le début de la douleur thoracique est inférieur à 12h et à fortiori inférieur à 2h il est recommandé de thrombolyser le patient et de l'adresser dans un centre de cardiologie interventionnelle. Nous avons comparé pour les années 2002 (avant la conférence), 2006 (pendant) et 2008 (après), les SCA ST+<2h du registre e-MUST traités par thrombolyse pré-hospitalière à ceux traités par angioplastie primaire. Ceux bénéficiant d'une angioplastie primaire ont été répartis en délai porte-porte cardio<45 min et >45 min. Pour chaque sous-groupe, le délai médian entre le début de la douleur thoracique et le traitement (injection du thrombolytique ou passage du guide) ont été calculés. Résultats: IDF 2002 2006 2008 p SCA ST+<24 h 1806 1618 1689 SCA ST+<2 h 1029 (57%) 1015 (63%) 1042 (62%) =0, 002 SCA ST+<2 h décision désobstruction 940 (91%) 959 (94%) 989 (95%) =0, 01 1/Soit thrombolyse pré-hospitalière (TPH) 373 (44%) 318 (36%) 196 (21%) <0, 001 Délai médian DT-TPH (minutes) 85 80 80 =0, 018 2/Soit angioplastie primaire avec délai porte-porte cardio<45' 114 (12%) 173 (19%) 243 (26%) <0, 001 Délai médian DT-guide (minutes) 135 128 131 =0, 54 3/Soit angioplastie primaire avec délai porte-porte cardio>45' 358 (42%) 403 (45%) 481 (53%) <0, 001 Délai médian DT-guide (minutes) 160 161 160 =0, 410 Discussion: La proportion de SCA ST+ pris en charge en moins de 2h augmente de 57% en 2002 à 62% en 2008. Le taux de décision de désobstruction en pré-hospitalier augmente de 91% en 2002 à 95% en 2008. Les délais médians « début de la douleur thoracique-traitement » sont stables pour l'angioplastie primaire. La thrombolyse pré-hospitalière diminue de 44% en 2002 à 21% en 2008. La proportion de SCA ST+<2h, traités par angioplastie primaire qui arrivent en plus de 45 min en salle de cathétérisme cardiaque augmente de 42% en 2002 à 53% en 2008. Le délai médian « début de la douleur thoracique-traitement » est de 80 min pour les thrombolysés et de 160 min pour les angioplasties primaires qui arrivent en plus de 45 min en salle de cathétérisme cardiaque. Conclusion: Le registre e-MUST permet de mesurer l'impact clinique des recommandations de la conférence de consensus sur la prise en charge pré-hospitalière des SCA ST+<2h. On retient une prise en charge de plus en plus précoce des SCA ST+ et un taux record de décision de désobstruction en pré-hospitalier. Ces résultats positifs s'inscrivent probablement dans le bénéfice de la dynamique continue d'un registre. Cependant, le délai porte–porte cardio est sous-estimé par les médecins pré-hospitaliers. Le registre e-MUST permet une réflexion sur l'estimation des délais et les choix thérapeutiques, pour optimiser et suivre le taux de patients reperfusés dans les délais.